Organized Sunday-school work in America, 1905-1908 triennial survey of Sunday-school work including the official report of the twelfth International Sunday School Convention, Louisville, Kentucky, June 18-23, 1908. (Executive Committee of the International Sunday-School Association, 1908)
Quadrennial, 1918-